2011
DOI: 10.1016/j.ajpath.2011.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Promotes Early but Attenuates Established Disease in Crescentic Glomerulonephritis in Mice

Abstract: T helper (Th)17 cells might contribute to immunemediated renal injury. Thus, we sought to define the time course of IL-17A-induced kidney damage and examined the relation between Th17 and Th1 cells in a model of crescentic anti-glomerular basement membrane glomerulonephritis. Renal injury and immune responses were assessed in wild-type and in IL-17A-deficient mice on days 6, 14, and 21 of disease development. On day 6, when mild glomerulonephritis developed, IL-17A-deficient mice were protected from renal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 54 publications
5
45
1
Order By: Relevance
“…[18][19][20] In glomerulonephritis, a biphasic response with protection against renal injury in the early phase and aggravation in the later phase was found in IL-17-deficient mice. 21 A protective effect of IL-17 has also been suggested in aortic aneurysm formation, and low circulating IL-17 levels were associated with a higher cardiovascular risk after myocardial infarction. 22,23 IL-17 deficiency is not equivalent to inhibiting Th17 cell generation.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In glomerulonephritis, a biphasic response with protection against renal injury in the early phase and aggravation in the later phase was found in IL-17-deficient mice. 21 A protective effect of IL-17 has also been suggested in aortic aneurysm formation, and low circulating IL-17 levels were associated with a higher cardiovascular risk after myocardial infarction. 22,23 IL-17 deficiency is not equivalent to inhibiting Th17 cell generation.…”
Section: Discussionmentioning
confidence: 99%
“…Paust et al demonstrated that Th17 cells contributes to anti-GBM GN with the use of IL-23p192/2 and IL-17A2/2 mice (87), whereas Odobasic et al examined the reciprocal relationship between Th1 and Th17 and demonstrated that early nephritogenic responses were mediated by Th17 cells, but late disease is Th1 dependent. They also demonstrated that each Th subset counterregulated the other (88). Furthermore, Steinmetz et al used mice with gene deletion of RORg-t, the key Th17 transcription factor, to confirm the participation of the CD41 Th17 subset (89).…”
Section: Autoimmune Crescentic Glomerulonephritis Lupus Nephritismentioning
confidence: 99%
“…First, T H 17 cells and, subsequently, T H 1 cells migrate into the kidney and promote renal tissue injury. [11][12][13] The role of neutrophils in the T cellmediated phase (starting from day 5) is largely unknown. We therefore assessed the time course of renal neutrophil infiltration using immunohistochemical staining for the neutrophil marker Gr1 (Ly6C/Ly6G) ( Figure 1A).…”
Section: Time-and Compartment-specific Infiltration Of Neutrophils Inmentioning
confidence: 99%